Business Development Strategy for Snack Processing in Micro Industries through Strengthening Marketing Aspects - Arbainah, Siti -; Handayani, Jati -; Sugiarti, Sugiarti - (Admisi dan Bisnis, 2019)
Kendal's specialty snacks are one of the culinary heritages that need to be preserved. Very reasonable to be developed. The purpose of this study is to formulate a business development strategy by increasing strengths and reducing the weaknesses of marketing aspects to seize available market opportunities. The object of the research is the micro industry member of KUB Bina Usaha in Jambearum Patebon Tourism Village, Kendal Regency, which produces Kendal typical snacks "emping ketan". The survey results show that the micro industry is facing business problems including market demand in certain seasons fluctuating very high; increasingly fierce market competition; potential markets have not been served optimally. Marketing is still passive, just waiting for buyers to come. Based on these problems, through observation and FGD with the help of questionnaires and subsequently the data is processed qualitatively by classification methods, the strengths, weaknesses and opportunities of the micro industry can be mapped. A suitable strategic approach is the SO (strength-Opportunity) and WO (Weakness-Opportunity) strategy. Strategies that implement efforts to seize opportunities by utilizing strengths and reducing weaknesses. The micro food processing industry can increase promotion and expand networks by utilizing technological advances such as the internet, conducting training and marketing management assistance, redesigning product packaging to make it more attractive and complementing packaging equipment that can improve quality to seize the opportunities available